![x^2+3x+18 = (x+3)(x+6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/wt2kl9ixoxnxfvhu9vzm6hwpjet8v1elii.png)
↝ The error here is that (x+3)(x+6) doesn't make 3x in the middle here.
↝ From (x+a)(x+b) = x²+bx+ax+ab = x²+(a+b)x+ab
Now we let a = 3 and b = 6
Let's check the answer.
Given a = 3 and b = 6 (From the polynomials given.)
(x+a)(x+b) = x²+(a+b)x+ab
(x+3)(x+6)=x²+(3+6)x+(3*6)
(x+3)(x+6)=x²+9x+18
As you can see that the error here is that (x+3)(x+6) doesn't make 3x in the middle of polynomial. Therefore the error here is only 3x as proven.